Soft chemistry of metastable metal chalcogenide nanomaterials. (4th May 2021) - Gu, Chao; Xu, Hou-Ming; Han, Shi-Kui; Gao, Min-Rui; Yu, Shu-Hong
Abstract : This review summarizes the latest advances in design principles based on metastable metal chalcogenide nanomaterials (MCNs), together with corresponding soft chemical transformation rules to prepare or modify MCNs with novel or enhanced properties. Abstract : The metastable nature of metal chalcogenide nanomaterials (MCNs) provides us with fresh perspectives and plentiful grounds in the search of new strategies for physicochemical tuning. In the past decade, numerous efforts have been devoted to synthesizing and modifying diverse emerging MCNs based on their "soft chemistry", that is, gently regulating the composition, structure, phase, and interface while not entirely disrupting the original features. This tutorial review focuses on design principles based on the metastability of MCNs, such as ion mobility and vacancy, thermal and structural instability, chemical reactivity, and phase transition, together with corresponding soft chemical approaches, including ion-exchange, catalytic growth, segregation or coupling, template grafting or transformation, and crystal-phase engineering, and summarizes recent advances in their preparation and modification. Finally, prospects for the future development of soft chemistry-directed synthetic guidelines and metastable metal chalcogenide-derived nanomaterials are proposed and highlighted.